2012
DOI: 10.1371/journal.pone.0053004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fading Media for Live Cell GFP Imaging

Abstract: Photostability is one of the most important characteristic of a dye for fluorescence microscopy. Recently we demonstrated that vitamins present in imaging media dramatically accelerate photobleaching of Enhanced Green Fluorescent Protein (EGFP) and many other green fluorescent and photoactivatable proteins. Here we tested all vitamins of commonly used media (such as Dulbecco's Modified Eagle Medium, DMEM) one-by-one and found that only two vitamins, riboflavin and pyridoxal, decrease photostability of EGFP. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 11 publications
1
44
0
Order By: Relevance
“…In particular, F12 contains greatly decreased concentrations of riboflavin and pyridoxine (11- and 67-fold, respectively). These differences appear to be most important, as we previously demonstrated that these vitamins reduce EGFP photostability dramatically (4, 5). …”
mentioning
confidence: 91%
See 3 more Smart Citations
“…In particular, F12 contains greatly decreased concentrations of riboflavin and pyridoxine (11- and 67-fold, respectively). These differences appear to be most important, as we previously demonstrated that these vitamins reduce EGFP photostability dramatically (4, 5). …”
mentioning
confidence: 91%
“…To improve photostability of fluorescent proteins, site-directed and random mutagenesis have been used extensively (2). As an alternative approach, optimization of imaging medium composition has been suggested recently (4, 5). This approach is based on the fact that GFPs can participate in light-driven redox reactions with intracellular electron acceptors that result in oxidative green-to-red photoconversion (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanistically, Shiga toxin is internalized by the cells via Gb3 receptors and cleaves the N-glycosidic bond of adenine at nucleotide position 4324 in the 28s rRNA of the 60s ribosomal subunit (Endo et al 1998). Elimination of this one adenine residue blocks peptide chain elongation and inhibits protein synthesis.…”
Section: Introductionmentioning
confidence: 99%